2018
DOI: 10.1149/2.0331802jes
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of LiTfO/TEGME and LiTfO/DME Electrolytes in Li-O2Batteries

Abstract: In this work we discuss the degradation chemistry on carbon-free electrodes of two ether based electrolytes for Li-O 2 batteries, i.e. tetraethylene glycol dimethyl ether (TEGDME) and dimethoxy ethane (DME) with lithium trifluoromethane sulfonate (LiTfO) as salt. To this aim we developed an all-metallic positive electrode by electrodeposition of a gold dendritic film on a nickel foam (Au@Ni). These carbon-free electro-catalytic electrodes have been used to investigate the degradation chemistry of the electroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 73 publications
2
31
0
Order By: Relevance
“…Along the same lines as reported by several authors for Li‐ion batteries, this peak is interpreted as the residual intercalated Na ions into the graphitic framework (NaxC) of the HC ,. Another difference from the pristine HC is that the peak at 286.3–286.4 eV (cyan), previously assigned to CH 2 −CF 2 (dark green), is now attributed to alcohol/ether/epoxy groups and its area was free to vary during the curve fittings. The contribution of CH 2 −CF2 to this peak is challenging to quantify due to the increment of the −CF 2 − signals caused by the decomposition of fluorinated species (i. e. FEC and NaTFSI).…”
Section: Resultssupporting
confidence: 75%
“…Along the same lines as reported by several authors for Li‐ion batteries, this peak is interpreted as the residual intercalated Na ions into the graphitic framework (NaxC) of the HC ,. Another difference from the pristine HC is that the peak at 286.3–286.4 eV (cyan), previously assigned to CH 2 −CF 2 (dark green), is now attributed to alcohol/ether/epoxy groups and its area was free to vary during the curve fittings. The contribution of CH 2 −CF2 to this peak is challenging to quantify due to the increment of the −CF 2 − signals caused by the decomposition of fluorinated species (i. e. FEC and NaTFSI).…”
Section: Resultssupporting
confidence: 75%
“…Unfortunately, this technology is facing many challenges: During charge and discharge, reactive oxygen species like singlet oxygen and superoxide are formed, which are leading to side reactions with carbon electrodes and the electrolyte. [1][2][3][4][5][6] Moreover, the main discharge products in LiÀ O 2 , NaÀ O 2 , KÀ O 2 and MgÀ O 2 batteries are Li 2 O 2 , NaO 2 , KO 2 and MgO 2 , which are electronically insulating. [7][8][9][10][11][12][13][14][15] For the electrochemical deposition of Li 2 O 2 , Bondue et.…”
Section: Introductionmentioning
confidence: 99%
“…[24] In 2016 by Gao et al suggested a mechanism for the mediated ORR by the electrochemically formed DBBQ monoanion: [24] DBBQ sol ð Þ þe À ! DBBQ À ðsolÞ (1) Li þ sol ð Þ þDBBQ À ðsolÞ ! Li � � � DBBQ ðsolÞ (2) Li� � �DBBQ ðsolÞ þO 2ðsolÞ G…”
Section: Introductionmentioning
confidence: 99%
“…[16] The origin of the large current density increasef rom 4.3 Vm ay be owing to electrolyte degradation initiated by O 2 radicals. [17] The calculated charge density of GC (Q O 2 ÀQ N 2 )w as À6.04 mC cm À2 for the reduction reactiona nd 1.56 mC cm À2 for the oxidation reaction. To check the feasibility of carboncoated Ni substrates, CV profiles of CNP were measured using the same experimental conditions applied for the GC electrode under flow of N 2 and O 2 .T he calculated charge density (Q O 2 ÀQ N 2 )f or CNP was À1.62 mC cm À2 fort he reduction reaction, whichi sm ainly attributable to the enhanced negative current density below 2.5 V. However,arelatively low current density of 0.18 mC cm À2 was obtained from the oxidation reaction with very broad current peaks centered at 3.5a nd 4.1 V.…”
mentioning
confidence: 99%
“…The Ramans pectra obtained on the three different sites were identical, showing aGpeak at approximately 1600 cm À1 and al argely broadened Dp eak at approximately 1350 cm À1 ,w hich are commonly observable fora morphous carbon by virtue of the sp 2 -hybridization disorder. [17] The calculated charge density of GC (Q O 2 ÀQ N 2 )w as À6.04 mC cm À2 for the reduction reactiona nd 1.56 mC cm À2 T he calculated charge density (Q O 2 ÀQ N 2 )f or CNP was À1.62 mC cm À2 fort he reduction reaction, whichi sm ainly attributable to the enhanced negative current density below 2.5 V. However,arelatively low current density of 0.18 mC cm À2 was obtained from the oxidation reaction with very broad current peaks centered at 3.5a nd 4.1 V. [13,14] Also, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) in dimethoxyethane (DME) is knownt ob eo ne of the mosts table electrolytesf or Li-O 2 applications and forms Li 2 O 2 on the first discharge.…”
mentioning
confidence: 99%